Penetration and impact of COVID-19 in long term care facilities in England: population surveillance study. (1st September 2021) - Chudasama, Dimple Y; Milbourn, Hannah; Nsonwu, Olisaeloka; Senyah, Francis; Florence, Isaac; Cook, Bryony; Marchant, Elizabeth; Blomquist, Paula Bianca; Flannagan, Joe; Dabrera, Gavin; Lewis, James; Lamagni, Theresa
Abstract: Background: Long-term care facilities (LTCF) worldwide have suffered high rates of COVID-19, reflecting the vulnerability of the persons who live there and the institutional nature of care delivered. This study describes the impact of the pandemic on incidences and deaths in LTCF across England. Methods: Laboratory-confirmed SARS-CoV-2 cases in England, notified to Public Health England from 01 Jan to 25 Dec 2020, were address-matched to an Ordnance Survey reference database to identify residential property classifications. Data were analysed to characterize cases and identify clusters. Associated deaths were defined as death within 60 days of diagnosis or certified as cause of death. Results: Of 1 936 315 COVID-19 cases, 81 275 (4.2%) and 10 050 (0.52%) were identified as resident or staff in an LTCF, respectively, with 20 544 associated deaths in residents, accounting for 31.3% of all COVID-19 deaths. Cases were identified in 69.5% of all LTCFs in England, with 33.1% experiencing multiple outbreaks. Multivariable analysis showed a 67% increased odds of death in residents [adjusted odds ratio (aOR): 1.67, 95% confidence interval (CI): 1.63–1.72], compared with those not residing in LTCFs. A total of 10 321 outbreaks were identified at these facilities, of which 8.2% identified the first case as a staff member. Conclusions: Over two-thirds of LTCFs have experienced large and widespread outbreaks of COVID-19, and just under one-third of all COVID-19 deaths occurring in this setting in spite of early policies. A key implication of our findings is upsurges in community incidences seemingly leading to increased outbreaks in LTCFs; thus, identifying and shielding residents from key sources of infection are vital to reduce the number of future outbreaks.